PENGARUH KREDIT BERMASALAH, KECUKUPAN MODAL DAN LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS PADA PT BANK PEMBANGUNAN DAERAH BALI DI BALI - Herlambang, Putu Gede Denny; Sukanti, Ni Ketut; Geriadi, Made Ayu Desy; Juliantari, I Dewa Ayu Alit (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
This study aims to determine the effect of non-performing loans, capital adequacy and loan to deposit ratio on profitability at PT Bank Pembangunan Daerah Bali in Bali. This research is categorized as quantitative research. This study uses financial reports at PT Bank Pembangunan Daerah Bali for the quarterly period from 2013-2020, the sampling technique uses a sampling technique so that the saturated sample obtained in this study is 32. The data analysis technique used is the classical assumption test, linear regression analysis multiple, determination analysis, partial test (t-test) and simultaneous test (F-test). The results showed that Non-Performing Loan had a negative and significant effect on Profitability. Capital Adequacy Ratio has a positive and significant effect on profitability, and Loan to deposit ratio has a positive and significant effect on profitability. Non-Performing Loans, Capital Adequacy Ratio and Loan to Deposit Ratio have a significant simultaneous effect on profitability at PT Bank Pembangunan Daerah Bali in Bali.